The Role of Celebrity Endorsers and Digital Marketing: Consumer Purchase Decisions on Tiket.Com with Purchase Intentions as an Intervening Variable - C. Catur Widayati; Hendra Wiyanto; Herlina Budiono; Anisah Anisah (Dinasti Publisher, 2024)
This study aims to investigate the influence of celebrity endorsers and digital marketing promotions on consumer purchasing decisions for Tiket.com products, with purchase intention as an intervening variable. Quantitative method was employed in this study. The population studied consisted of Tiket.com users in Jakarta, using purposive sampling technique with Hair's formula, resulting in a sample size of 160 individuals. The results of the study indicate that celebrity endorsers have a significant positive influence on purchase intention, as do digital marketing promotions. Additionally, celebrity endorsers also have a significant positive influence on purchase decisions, as do digital marketing promotions. Furthermore, purchase intention also acts as an intervening variable in purchase decisions.